2021
DOI: 10.1017/s0021859621000654
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy, environmental safety and synergistic impacts of biorational formulations against whitefly, leafhopper and blister beetle in organic okra ecosystem

Abstract: Whitefly (Bemisia tabaci Gennadius), leafhopper (Amrasca biguttula biguttula Ishida) and large yellow-banded blister beetle (Mylabris phalerata) cause considerable damage to okra, especially under organic farming. Thus, the present study was carried out to test the bioefficacy and environmental safety of six naturally derived components [indigenous water plant extracts, i.e. chilli (Capsicum annum), garlic (Allium sativum L.) and neem (Azadirachta indica A. Juss.) along with cow urine in three different combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…The solution was then stored at 4 • C in an airtight clean container before use. The extract was sprayed at three different doses (20,40, and 60 mL/L) [37].…”
Section: Chili Pod Extractmentioning
confidence: 99%
“…The solution was then stored at 4 • C in an airtight clean container before use. The extract was sprayed at three different doses (20,40, and 60 mL/L) [37].…”
Section: Chili Pod Extractmentioning
confidence: 99%
“…A combination of cow dung with urine, ash, slurry, or vermiwash significantly reduced insect pest populations on brinjal [141,142]. The application of chili, garlic, and neen leaf extracts in cow urine on okra reduced the whitefly and other pests' population [143].…”
Section: Fermented Curd Watermentioning
confidence: 99%
“…belongs to the family Phyllanthaceae with geoavaliability in India, Sri Lanka, and other parts of South Asia and is also well known for its pharmacological usage. Preliminary studies have indicated the insecticidal potential of C. collinus against leafhoppers, whiteflies [10], and stored-grain pest [11]. The insecticidal activity was attributed to the presence of diverse secondary metabolites, such as triterpenoids, alkaloids, and flavonoids, and some plant-specific compounds like collinusin and cleistanthins [12].…”
Section: Introductionmentioning
confidence: 99%